Pengaruh Biblioterapi Dengan Buku Cerita Bergambar Terhadap Tingkat Kecemasan Efek Hospitalisasi pada Anak Prasekolah - Apriza Apriza (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
The numbers of the hospitalized children in the last two decades have been increased rapidly. The increasing of the percentage of the hospitalized children became more serious and more complex than the previous years. Hospitalization might causes anxious on the children. The children became increasingly anxious and might affect the healing process. Therefore, to decrease the children’s anxiety during the healing process, the use of the book as a therapy media, known as Bibliotherapy is suggested. This research is aimed at identifying the effect of Bibliotherapy by using storybooks on the anxiety level of hospitalization effect on preschool children in children’s room. This research employed Quasi-Experimental with One Group pre-test and post-test design, and the total sample was 19 respondents. The sampling technique was accidental sampling. The instruments used in this research were questionnaire and observation. The data were analyzed through univariat and bivariate. The findings showed that the average score on the level anxiety before treated by Bibliotherapy by using the storybooks was 23.2, while after giving the therapy was 18.6. The T-test obtained p+0,001 (p0.05), it means that Ho is rejected, there is a relationship between the effect of Bibliotherapy by using story books on the children’s level of anxiety as the effect of the hospitalization on the preschool children in children’s room at RSUD Bangkinang. It is expected for the Hospital to give therapy program while children care by Bibliotherapy by using the storybooks to decrease the children’s anxiety.